Model of Electromagnetic Emitter Based on a Stream of Single Electrons inside Curved Carbon Nanotube - N. A. Poklonski; S. A. Vyrko; A. T. Vlassov; A. I. Siahlo; S. V. Ratkevich (Приборы и методы измерений)
The problems of elaboration and application of microand nanometer sized antennas for the generation and reception of electromagnetic radiation is still relevant in both fundamental and applied aspects. With decreasing antenna size, the frequency of electromagnetic radiation increases, and its power decreases. To increase the radiation power, the periodic (in space) electrodynamic structures are used. The aim of the work is to find the possibility of application of injection and (quasi)ballistic drift of single electrons inside curved carbon nanotubes for emission of electromagnetic waves in the microwave range and to determine the parameters of the radiating system that affect the radiation power.By the calculation within the framework of classical electrodynamics it is shown the possibility in principle of generation of electromagnetic radiation of the gigahertz range by a stream of single electrons inside a hollow curved dielectric carbon nanotube.It was found that the spectrum and power of this radiation can be controlled by varying the electron flux density, length and curvature of the hollow nanotube.The results of the work can be applied for elaboration of a microminiature emitter of microwave electromagnetic radiation based on a curved carbon nanotube in the engineering of contactless probe microscopy.